Perception of brand value and motivation to collect second goods - Tiarawati, Monika; Widyastuti, Widyastuti; Artanti, Yessy; Frianto, Agus; Paramita, Sista (Technium Social Sciences Journal, 2022)
This study aims to empirically examine the perceived value of a brand on the behavior of buying second goods and the motivation for buying behavior of second goods. Second-hand goods or used goods are goods that are not used or are no longer needed by the owner, but not all of these goods cannot be used anymore. Second goods become an alternative in getting cheap goods without reducing the usefulness and satisfaction of the type of goods needed. The majority of people state that there is no need to buy new goods if Second goods can still be used and are suitable for use. In this study, researchers distributed online questionnaires to 100 respondents, namely people who had bought secondhand goods, and then analyzed using the Multiple Regression analysis tools. The results showed that there was an influence of perception of brand value and motivation to collect variables on the decision to buy second-hand goods.